Grit blasted aggregates of hydroxyl apatite functionalized calcium carbonate in occluding dentinal tubules - S. Välimaa; L. Perea-Lowery; J.-H. Smått; J. Peltonen; T. Budde; P. K. Vallittu (Elsevier Ltd., 2022)
Objectives
This study aimed to investigate the effects of using hydroxyl apatite functionalized calcium carbonate (FCC) particles on occluding dentinal tubules.
Methods
Dentine specimens extracted from eighteen human molars with exposed dentinal tubules were divided into three groups (n = 6/group): a) Cut surface with smear layer; b) EDTA (smear layer removed with 17% EDTA for 1 min); and c) Grit blasted functionalized calcium carbonate (FCC) with and air pressure of 280 kPa. Microscopic dentinal tubule occlusion, tubule diameter and tubule area were evaluated using scanning electron microscopy (SEM) before and after grit blasting. Biomineralization of specimens was carried out in a simulated body fluid (SBF). Elemental analysis of occluding materials was carried out using energy-dispersive X-ray spectroscopy (EDX). X-ray diffraction (XRD) analysis was performed to demonstrate the crystal structure of the biomineralized layer on dentine.
Results
FCC particles showed penetration into the dentinal tubules by breakage of their original particle shape and size. EDTA treated surface had higher number and larger size tubules than those with smear layer or grit blasted (p < 0.005). SEM-EDX analysis revealed mineral precipitation of calcium phosphate on the SBF immersed dentin specimens. XRD analysis showed typical crystal structure of hydroxyl apatite for the biomineralized surface layer on dentine.
Conclusions
Grit blasted FCC particles initially occluded effectively the opened dentinal tubules and biomineralization occurred in tubules primarily occluded by the FCC particles. However, in the optimal in vitro conditions in SBF, no difference between biomineralization was found between the grit blasted surface and the control surface.
Clinical significance
Several materials and methods have been established for treatment of dentinal hypersensitivity although a golden standard treatment has not been discovered. Grit blasted functionalized calcium carbonate has a potential to occlude and remineralize exposed dentinal tubules. This could offer a more biological approach on treatment of dentin hypersensitivity.